(untitled) - Shirabe, Raisuke (Nagasaki, 2002)
This publication is an English translation of the diary of the late Dr. Raisuke Shirabe, professor of surgery at Nagasaki Medical University. Handwritten in a hardcover B5-size notebook, the original diary begins on August 9, 1945, the day that an atomic bomb completely destroyed and burned the buildings of Nagasaki Medical University and killed approximately 900 faculty members, administrative staff and students, and it ends on October 26, 1945 with a clipping of a newspaper article reporting the re-establishment of Nagasaki Medical University
Keywords: Chiến tranh thế giới, 1939-1945,World War, 1939-1945,Japan,Nhật Bản; Câu chuyện cá nhân, tiếng Nhật.,Personal narratives, Japanese; Nagasaki-shi.,Nagasaki-shi.